A Study of Academic Achievement of School Students having illiterate and literate parents - Kaur, Malkeet (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2011)
The study aims to study the academic achievement of school students having illiterate and literate parents. The sample of the study comprised of 100 school students from Hoshiarpur district of Punjab. The findings indicated that students having literate parents scored higher than the students having illiterate parents.